Medical clearance for participation in sports: the way to improvements - G. Makarova; L. Porubayko; S. Yurev (National Electronic Information Consortium (NEICON), 2020)
Ever-increasing prevalence of medical emergencies and sudden deaths of both adult and young athletes necessitates improvement in system of eligibility in sports. The current system involves two detailed medical screenings (DMS) of athletes every year that can be regarded only as a basic medical permission with a number of weak points due to the absence of adequate amount of data at initial screening in childhood. For greater efficiency the system should incorporate subsequent physical examination per differentiated protocols (according to the actual risk factors such as past medical history, injuries and their potential long-lasting consequences, nonfunctional overreaching etc.) with standard procedures of examination considering possible complications and also repeated participation evaluations (with emphasis on prevention of cardiac emergences) as the third stage in addition to DMS.